A Perceived Zone of Certainty and Uncertainty: Propositions for Research Development - Phan, Huy P.; Ngu, Bing H. (Frontiers in Psychology, 2021)
Possessing expert schemas is a positive feat that may yield different types of adaptive outcomes (e.g., informing procedural understanding that may result in a student skipping a few of the solution steps involved). Limited schemas, in contrast, may deter progress of a novice learner, limiting his/her capability to flourish. Taken as a whole, it may be concluded that expert schemas are more advantageous than novice schemas, differentiating learners in terms of expert and novice. Having said this, however, more recently, researchers have argued that possessing expert schemas could serve as deterrence. Recently, researchers have acknowledged a theoretical concept known as cognitive entrenchment, which is defined as a high level of stability in domain schemas. This description interestingly suggests that “entrenchment” or “situated fixation” of a course of action (e.g., a subject matter) could hinder the progress and learning experience of a person, namely—his/her inability and/or unwillingness to adapt to a new context, and/or his/her inflexibility and insistence to stay on course without any intent to change. One example of cognitive entrenchment is observed in professional football, wherein it has been argued that some football coaches are cognitively entrenched within their expert schemas, resulting in their demised game plans and strategic acumen. We advance the study of cognitive entrenchment by proposing an alternative viewpoint, which we term as the “perceived zone of certainty and uncertainty.” This proposition counters the perspective of cognitive entrenchment by arguing that it is cognitive appraisal, judgment, mental resolute, and determination of a person in cognitive certainty of his/her success or failure, or the cognitive uncertainty of success or failure, that would explain the notion of inflexibility and/or unwillingness to adapt, and/or insistence to stay on course without any attempt to deviate. Moreover, we rationalize that certainty of success or failure would closely associate with a feeling of comfort, whereas uncertainty would associate with his/her feeling discomfort. In this analysis, we strongly believe that willingness to change and adapt, reluctance and insistence to remain on course, and/or inclination to embrace flexibility may not necessarily relate to the concept of cognitive entrenchment; rather, inflexibility and/or reluctance to change for the purpose of adaptation has more to do with the desire of a person to seek a state of comfort. Finally, our conceptual analysis of cognitive entrenchment also considers an interesting theoretical concept, which we termed as “perceived optimal efficiency.” Perceived optimal efficiency, similar to cognitive relevance theory, is concerned with the relationship between minimum investment of time, effort, cognitive resources, etc., and an optimal best outcome. The issue for discussion, from our point of view, is related to the extent to which the certainty of success or failure would associate with perceived optimal efficiency.